Anti-Glycoprotein Ib/IX and llb/llla Antibodies in Patients with Antiphospholipid Antibodies - Galli, Monica; Daldossi, Maria; Barbui, Tiziano (Thrombosis and Haemostasis, 1994)
Antiphospholipid antibodies, namely lupus anticoagulant (LA), anticardiolipin (aCL) type A and type B antibodies, are frequently associated with immune-mediated thrombocytopenia. Antiphospholipid antibodies have been suggested to bind to the phospholipids of the platelet membrane, thus participating to the process of platelet destruction, which leads to thrombocytopenia. However, a clear antiphospholipid (aPL) demonstration of such a role has never been given for antibodies. Conversely, autoantibodies directed against membrane-associated glycoproteins (GP) have been shown to be pathogenet- ically linked to the development of thrombocytopenia in patients with idiopathic thrombocytopenic purpura. For this reason, we have measured anti-GPIb/IX and GPlIb/IIIa IgG in the plasma of 68 patients with aPL antibodies by ELISA. The monoclonal antibody-specific immobilization of platelet antigen (MAIPA) assay was used.Twenty-seven out of 68 patients with antiphospholipid antibodies (40%) had increased plasma levels of anti-GP antibodies. In particular, 7 of them had elevated anti-GPIIb/IIIa levels only, 6 had anti-GPIb/IX antibodies only, whereas in the remaining 14 cases both types of autoantibodies were found elevated. The level of anti-GP antibodies in plasma did not correlate with age, sex, clinical associated conditions, history of thrombosis, IgG aCL titer or the presence of a phospholipid- dependent inhibitor of coagulation. In contrast, a statistically significant association between thrombocytopenia and high anti-GP antibody titer was observed (p = 0.0458).To establish whether there was cross-reactivity between antiphospholipid and anti-GP antibodies, adsorption experiments were performed using eardiolipin-containing liposomes or washed, normal, resting platelets. When patients’ plasma was mixed with resting washed platelets, only anti-GP antibodies were adsorbed on platelet membrane and subsequently eluted from platelets. Conversely, binding to cardio- lipin-containing liposomes but not to platelet surface was demonstrated for antiphospholipid antibodies.In conclusion, our data indicate that high levels of anti-platelet glycoprotein antibodies are more frequently found in patients with antiphospholipid antibodies and thrombocytopenia and that they might be responsible, more than LA and/or aCL antibodies, for the development of thrombocytopenia.